Counseling and Making Environment Friendly Cleansing Using Fruit and Flower Extractsin The Framework of Increasing The Welfare of Teachers and Preparing Independent Entrepreneurship For SMA-IT Studentsriyadhussholihiin Islamic Boarding School- Cimanuk-Pandegelang - I G A Arwati; Hari Setiyawati; Gian Villany Golwa; Wiwit Suprihatiningsih; Erna Setiany; Yudhi Herliansyah; Siti Choiriah; Suharmadi Suharmadi; Safira Safira; Sri Purwaningsih; Puji Rahayu; Riri Pratiwi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This community service is carried out in the context of foreign cooperation where the partner is Professor Dr. Yusliza Mohd Yusoff from Universiti Malaysia Terengganu (UMT). We carry out this community service activity with the theme